Encoding sex ratio information: automatic or effortful? - Dillon, Haley Moss (Kansas State University, 2015)
Operational Sex Ratio (OSR: the ratio of reproductively viable males to females in a given population) has been theorized and studied as a construct that may influence behaviors. The encoding of sex ratio was examined in order to determine whether the cognitive process underlying it is automatic or effortful. Further, the current work examines whether OSR or Adult Sex Ratio (ASR: the ratio of adult males to females) is encoded. The current work involved four experiments; two using frequency tracking methodology and two using summary statistic methodology. Experiment 1 found a strong correlation between OSR of conditions and estimates of sex ratio. Participants in Experiment 1 were uninformed on the purpose of the experiment, thus the strong correlations between actual and estimated sex ratio suggest a level of automaticity. Experiment 2 found a strong correlation between the ASR of conditions and estimates, suggesting that individuals do not encode OSR over ASR. Experiments 3.a. and 3.b. demonstrated automaticity in estimates of sex ratio from briefly presented sets of faces, for two different durations: 1000ms and 330ms, the later of which is widely accepted as the length of a single eye fixation. Overall this work demonstrated a human ability to recall proportion of sexes from arrays of serially presented individuals (Experiments 1 and 2), and that ASR is encoded when participants are presented with conditions including older adults. This work found the encoding of sex ratio to be highly automatic, particularly stemming from the results of Experiments 3.a. and 3.b. Conclusions from this work help to verify previous research on sex ratio’s effect on mating strategies through evidence supporting the automatic nature of encoding sex ratio. Further, the current work is a foundation for future research regarding sex ratio, and leads to several proposals for future endeavors.
Keywords: Operational Sex Ratio; Frequency Tracking; Summary Statistics; Mating Strategies; Cognitive Psychology (0633)